Anti-hepatitis B Virus Activity of α-DDB-FNCG, a Novel Nucleoside-Biphenyldicarboxylate Compound In Vitro and In Vivo - Qinghua Yang; Xuejie Zhao; Wenquan Yu; Wu He; Xianzhen Fang; Limin Zang; Na Wan; Qingduan Wang; Liyun Zheng; Junbiao Chang (Elsevier, 2014)
Abstract.: A novel codrug, α-DDB-FNCG, was synthesized through coupling of α-biphenyl dimethyl dicarboxylate (α-DDB) and the nucleoside analogue FNCG, via an ester bond. The anti-HBV activity and hepatoprotective effects of this compound were investigated both in vitro and in vivo. In HBV-transfected HepG2.2.15 cell line, the secretion of HBsAg and HBeAg as well as the levels of extracellular and intracellular viral DNA were determined by ELISA and real-time fluorescent quantitative Polymerase Chain Reaction (FQ-PCR), respectively. In DHBV-infected ducks, the viral DNA levels in serum and liver were determined by FQ-PCR. In addition, the levels of alanine transaminase (ALT) and aspartate aminotransferase (AST) in both serum and liver were also examined. The improvement of ducks' livers was evaluated by histopathological analysis. It has been demonstrated that α-DDB-FNCG could suppress the levels of HBV antigens and viral DNA in a time- and dose-dependent manner in the HepG2.2.15 cell line. Furthermore, this codrug could also significantly inhibit the viral DNA replication and reduce the ALT and AST levels in both serum and liver of DHBV-infected ducks, with improved hepatocellular architecture in drug-treated ducks. In short, these results suggest that α-DDB-FNCG could be a promising candidate for further development of new anti-HBV agents with hepatoprotective effects. Keywords:: α-DDB-FNCG, hepatitis B virus, duck hepatitis B virus, hepatoprotective effect